A case of cutaneous Mycobacterium chelonae infection requiring a differential diagnosis of Mycobacterium stephanolepidis infection. Issue 2 (8th September 2022) - Iwasawa, Okuto; Kamiya, Koji; Suzuki, Takayuki; Watanabe, Shinya; Cui, Longzhu; Karube, Daiki; Kado, Soichiro; Maekawa, Takeo; Komine, Mayumi; Ohtsuki, Mamitaro
Abstract : Mycobacterium stephanolepidis is a rapidly growing mycobacterium, closely related to Mycobacterium chelonae . It was first reported in 2017, and whether it is infectious to humans is unknown. Here, we report a rare case of cutaneous M. chelonae infection requiring a differential diagnosis of M. stephanolepidis infection.